Effect of Specific Training and Functional Strength Training on Selected Corporeal and Psychomotor Variables among School Taekwondo Boys: The Impact of Specific and Functional Strength Training on Corporeal and Psychomotor Variables in School Taekwondo Boys (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of the study was to find out the effect of specific training and functional strength training on selected corporeal and psychomotor variables among school taekwondo boys. To achieve the purpose of the study, 45 school taekwondo boys were selected from various schools in Namakkal District, Tamilnadu. The age of the selected subjects were ranged from 14 to 16 years. The selected subjects for this study were randomly divided into three equal groups of 15 subjects each, Experimental GROUP-I specific training (STG), Experimental group-II Functional strength training (FSTG) and Control Group III (CG). The specific training and functional strength training was scheduled for 12 weeks prior and after the training for corporeal and psychomotor variables were put in-to statistical treatment using Analysis of Covariance (ANCOVA) to find out the significant mean differences. Scheffe s post hoc test was used to find out the paired mean differences. In all the cases the 0.05 level of confidence was fixed.